Liability of the Land Deed Official for the Forgery of Information and Documents Committed by the Parties Involved in the Creation of Deeds - Rakeen Putra Abdi; Ismunarno Ismunarno; Noor Saptanti (Siber International Journal of Advanced Law (SIJAL), 2025)
This legal research aims to find out the responsibility of the Land Deed Official for falsifying information and documents committed by the applicant in making the deed. The type of research used by the author is normative legal research. This research uses primary legal materials and secondary legal materials. Primary legal materials are obtained from legislation, official records or minutes in making legislation and judges' decisions, while secondary legal materials are obtained from legal dictionaries, books, journals and so on. The data collection technique used is literature study. The research results show that in making deeds, Land Deed Official must apply the principle of caution and ensure the validity of the documents submitted, as well as understand the legal implications of the information provided by the parties. Land Deed Official can be held accountable administratively, civilly or criminally if it is proven that it was negligent or participated in falsifying information and documents in making the deed.